Application of telepschiatry in the treatment of pathological gamblers during the COVID9 pandemic - Sbutega Filipović, Olivera; Jovanovic, Aleksandar; Maksimovic, Jadranka (Medicinski podmladak, 2023)
Pathological gambling is serious mental disorder and is the only behavioral addiction currently recognized by the American Psychiatric Association. The frequency od disorders caused by gambling and online gambling is increasing in countries around the world as well as the need of help in the purpose of therapy and treatment  for both patients and their families who are affected by this disease. The Covid19 pandemic has greatly affected the social life of the world´s population,as well as changes in the world of commercial gambling, disorders caused by gambling and the therapy of already diagnosed patients. Group family cognitive-behavioral therapy is one of the therapies of choice that is recognized and accepted for the pathology caused by gambling. The Covid19 pandemic has led to the interruption of the possibility of live group in psychiatric health institutions in the Republic of Serbia due to epidemiological measures aimed at suppresssing the infectious disease. Telepsychiatry found its way at a given moment in order to maintain the existing program and patients, but also to provide new therapeutic opportunities for the future.
Keywords: Key words:; pathological gambling, telepsychiatry, Covid19, mental health